The effects of expanding the generosity of the statutory sickness insurance system - Nicolas Ziebarth; Martin Karlsson (Institute for the Study of Labor (IZA), 2013)
This article evaluates an expansion of employer-mandated sick leave from 80 to 100 percent of forgone gross wages in Germany. We employ and compare parametric difference-in-difference (DID), matching DID, and mixed approaches. Overall workplace attendance decreased by at least 10 percent or 1 day per worker per year. We show that taking partial compliance into account increases coefficient estimates. Further, heterogeneity in response behavior was of great importance. There is no evidence that the increase in sick leave improved employee health, a finding that supports a shirking explanation. Finally, we provide evidence on potential labor market adjustments to the reform.
Keywords: H51; I18; J22; J32; 330; difference-in-differences estimation; sickness absence; generosity of social insurance; employer sick leave mandate; natural experiment; SOEP